Ayurvedic Management of Chronic Kidney Disease (Vrikka Vikara): A Case Study - Manish, Acharya; Richa; Singh, Manjeet; Rani, Tanu; Bhardwaj, Renu (International Research Journal of Ayurveda & Yoga, 2026)
Chronic kidney disease (CKD) is a progressive disorder characterized by gradual loss of renal function, accumulation of metabolic waste products, and increased risk of cardiovascular and systemic complications. In Ayurveda, CKD can be correlated with Vrikka Vikara and disorders involving Mutravaha Srotodushti, where impairment of kidney function is associated with Tridosha imbalance, particularly Vata and Kapha, along with the accumulation of Ama (metabolic toxins) and vitiation of Rakta and Meda Dhatu. A 48-year-old male with a known case of chronic kidney disease (diagnosed in July 2022) presented to Jeena Sikho Lifecare Limited Hospital, Derabassi, Punjab, on 07/05/2024, with multiple systemic manifestations. At the time of presentation, the patient exhibited generalized weakness (Daurbalya), fatigue (Shrama/Klama), foot pain (Pāda Śhūla), dyspnea on exertion (Shrama Janya Shwāsa), bilateral pedal edema (Ubhaya Pāda Śotha), mild facial puffiness (Mukha Śotha), frothy urine (Phenila Mutra), and nocturia (Naktamutratā). The patient was hospitalized for clinical monitoring and managed with Ayurvedic dietary and lifestyle interventions for ten days from 07/05/2024 to 17/05/2024. Laboratory parameters demonstrated significant improvement following the intervention. Blood urea decreased from 40.50 mg/dl to 17.50 mg/dl, serum creatinine from 1.91 mg/dl to 1.70 mg/dl, and uric acid from 8.74 mg/dl to 6.95 mg/dl. Lipid profile showed reduction in triglycerides (321.20 mg/dl to 201.47 mg/dl) and VLDL cholesterol (64.24 mg/dl to 40.29 mg/dl). Total bilirubin reduced from 1.82 mg/dl to 1.52 mg/dl, with stabilization of direct and indirect bilirubin levels, suggesting improved hepatic and metabolic homeostasis. DTPA renal scan revealed persistently compromised left kidney function (GFR 1.4–1.9 ml/min) and compensatory improvement in the right kidney (GFR 27.9–32.8 ml/min), with global GFR increasing from 29.4 ml/min to 34.7 ml/ min. This case demonstrates that comprehensive Ayurvedic management, incorporating dietary regulation, lifestyle modification, and patient-centered care, can lead to significant clinical and biochemical improvement in patients with chronic kidney disease, even in the presence of longstanding comorbidities such as hypertension. While the structural damage in the left kidney remained irreversible, the compensatory improvement in right renal function, along with enhanced metabolic and lipid parameters, underscores the potential of integrative approaches in supporting renal function and overall systemic health.